The Identification of Language Functions and Expressions Used by Waiters/Waitresess at Scusa Restaurant by Ayana Resort Jimbaran Bali - Nariswari, Komang Ayu; Paramarta, I Made Suta; Adijaya, Made Aryawan (STKIP Agama Hindu Singaraja, 2024)
This study aims at investigating the language functions and language expressions employed at Scusa Restaurant, located in Ayana Resort, Jimbaran, Bali. Through qualitative analysis, it explores how language is utilized in various aspects of the breakfast experience, including customer interaction, menu presentation, and service communication. This study used observation and interview for get the data. The observation and interview conducted with the subjects on 13 May 2024 until 5 June 2024. The data was analyzed using the theory of language functions and language expressions developed by Purnamaningsih (2020) and Sardianti (2020). This study found a total of 16 language functions and 16 language expressions that are commonly used by waiter and waitresses in handling guests during breakfast. The language functions include, greetings, asking for how many parties, asking for room number, asking for sitting place, sitting the guests, unfolding napkin, giving information about the buffet, offering coffee or tea, presenting menu, taking order, repeating order, serving food or coffee and tea, checking back, settling payment, thanking the guest, and wishing a good day. Each language function is expressed through various language expressions that are appropriate to the situation and conditions while serving guests. The findings reveal the strategic use of language to enhance customers satisfaction, reflect cultural values, and maintain a high standard of hospitality.